Bridging Design and Standardization: Structural Analysis and Optimization of Direct Screw Fastening in Automotive Thermoplastic Panels - Dineshwar, Rishi; El Masri, Modi (My University, 2026)
The automotive industry aggressively pushes for lightweighting. This accelerates the transition toward direct screw fastening into thermoplastic components. The primary goal aims to eliminate heavy, costly metal compression limiters. Applying legacy metallic fastening standards to viscoelastic polymers introduces a critical engineering conflict. High assembly torques risk immediate localized yielding under the screw head. Overly conservative torques jeopardize long-term joint stability. This thesis investigates and optimizes the structural limits of insert-free thermoplastic joints within automotive A-pillar and IC-ramp assemblies developed in collaboration with Volvo Cars. A fully integrated engineering workflow challenges existing conservative torque practices. The methodology synthesizes physical friction characterization, an evolutionary optimization framework, high-fidelity nonlinear finite element analysis (FEM), and destructive physical validation. The FEM incorporates 1000-hour viscoelastic creep. Feeding experimental friction data directly into the computational loop significantly enhances the predictive accuracy of the long-term structural models. A unifying structural principle emerges across the computational optimization, virtual simulations, and physical testing. Contact geometry dictates joint survivability entirely more than bulk material stiffness. Captive washers fundamentally transform the mechanical load path. They reduce localized contact pressure and drastically increase ultimate torque capacity. This geometric optimization allows all evaluated thermoplastic joints to safely withstand the strict 10 Nm Volvo Cars internal standard without requiring metal inserts. Transitioning from elongated oval clearance holes to minimized, circular geometries proves critical. This maximizes continuous bearing area and actively prevents macroscopic deformation. Significant variations in long-term durability exist across the tested material matrix. Rigid amorphous blends (PC-ABS) demonstrate excellent structural stability at ambient temperatures. They exhibit severe clamp load decay under elevated thermal conditions (60◦C). Glass-fibre reinforced matrices (PP-GF) provide superior long-term preload retention. The internal glass fibers mechanically arrest viscoelastic flow. Unreinforced polypropylene (PP) exhibits critical sensitivity to massive creep and structural collapse across all configurations. The algorithmic DOE confirms that standard M5 fasteners lack sufficient bearing area for structural interior trim. This establishes M6 hardware as the absolute necessary baseline. This research directly challenges internal company standards, exposing a broader disciplinary gap between complex polymer mechanics and rigid mechanical standardization. The absence of a shared technical language across engineering, standards, and production functions represents a systemic barrier, not unique to this case, that prevents evidence-based design rules from reaching the factory floor. By translating viscoelastic behaviour and algorithmic optimization into actionable design guidance, this work demonstrates how silo-breaking, crossfunctional frameworks can bridge that gap, offering a replicable model for insert-free thermoplastic fastening beyond the automotive context studied here.
Keywords: Thermoplastic fastening; preload retention; viscoelastic creep; finite element analysis; structural optimization; genetic algorithms; Design of Experiments; surrogate modelling; automotive joints; contact mechanics